Flower drum song [videorecording (DVD)] - Rodgers, Richard, 1902-1979 (Universal Studios Home Entertainment, 2006)
Set in San Francisco's Chinatown in the late 1950's. Pretty Mei Li has stowed away on a Chinese steamer with her professor father to become a mail-order bride for nightclub owner Sammy Fong. Sammy, however, is completely infatuated with saucy showgirl Linda Low, who is intent on making him jealous enough to propose to her. As Sammy sets out to assign his marriage contract (and Mei Li) to Wang Ta, a handsome college student living in Chinatown, complications, merriment, and many musical numbers ensue.